ABU AMPAS TEBU SEBAGAI ADSORBEN DAN APLIKASINYA PADA PUNGUT ULANG KROMIUM(VI) DALAM LIMBAH CAIR ELEKTROPLATING - CHOIRUNNISA, VIKA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
A research on adsorption of Cr(VI) using activated bagasse ash has been conducted. This study aimed to determine the ability of activated bagasse ash in Cr(VI) adsorption. Several adsorption parameters were studied include initial pH, adsorption kinetics and adsorption isotherms. The bagasse ash as characterized using X-Ray Diffraction (XRD), Infra Red Spectrophotometer (IR) and Gas Sorption Analyzer (GSA) techniques. The concentration of Cr(VI) was determined using UV-Vis Spectrophotometer at max 542 nm after complexing of Cr with 1,5-diphenylcarbazide 0,5%. The result showed that bagasse ash after washing with HCl 1 M and calcination at a temperature of 700 oC for 3 hours led to increased adsorbent surface area from 31,39 m2/g to 276,3 m2/g. Adsorption of Cr(VI) on bagasse ash optimum at pH 1 and equlibrium time at 4 hours. Adsorption of Cr(VI) followed the pseudo second order kinetic of Ho with value of k2 was 4,695×10-3 g/mg min. On the use of Langmuir adsorption isotherm model, the maximum adsorption capacity of activated bagasse ash was 46,08 mg/g and the adsorption energy was 24,356 kJ/mole, so it can be classified as chemisorption. The percentage adsorption of Cr(VI) in the electroplating liquid waste using bagasse ash at pH 1 was 48.89%.